2001
DOI: 10.4049/jimmunol.166.5.3606
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic Translation Initiation Factor-6 Enhances Histamine and IL-2 Production in Mast Cells

Abstract: Eukaryotic translation initiation factor (eIF)-6 is known to be important in ribosome biogenesis. Previously, we have discovered that eIF-6 mRNA is induced in lung in a murine model of asthma. We also found that there was enhanced eIF-6 expression in mast cells stimulated with PMA plus calcium ionophore. Therefore, we hypothesized that the induction of eIF-6 enhances the production of bioactive mediators by mast cells upon allergic stimulation. In the current study, we found that eIF-6 mRNA was rapidly induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The specific down-regulation of eIF6 in Lck −/− cells may result from a combination of multiple signaling defects. eIF6 has been shown to be up-regulated in mast cells by FceR1 crosslinking and to be inhibited by cyclosporin A (45), and Ca 2+ signaling is particularly compromised in the absence of Lck in both CD4 (15) and CD8 T cells (47). Additionally, eIF6 promoter activity has been shown to be regulated by GABP (48), an Etslike transcription factor partially regulated by ERK (49), which is less strongly activated in Lck −/− cells.…”
Section: Discussionmentioning
confidence: 99%
“…The specific down-regulation of eIF6 in Lck −/− cells may result from a combination of multiple signaling defects. eIF6 has been shown to be up-regulated in mast cells by FceR1 crosslinking and to be inhibited by cyclosporin A (45), and Ca 2+ signaling is particularly compromised in the absence of Lck in both CD4 (15) and CD8 T cells (47). Additionally, eIF6 promoter activity has been shown to be regulated by GABP (48), an Etslike transcription factor partially regulated by ERK (49), which is less strongly activated in Lck −/− cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cycling cells have higher eIF6 levels than post-mitotic cells [17]. Rapid induction occurs during mast cell activation [44], rupture of the epidermal barrier [77] or liver regrowth (unpublished data; Fig. 1).…”
Section: Introductionmentioning
confidence: 92%
“…Many studies on the mast cell line HMC1 and the pluripotent hematopoietic cell line UT7D1 have demonstrated that HDC-gene expression is subject to posttranscriptional control. Therefore, the chromosomal configuration and methylation of the HDC-promoter is likely to account for its cell-specific expression [46,47]. It has also been reported that PMA stimulates a strong increase in HDC activity in UT7D1, which is affected by actinomycin D, and that is not paralleled by enhanced HDC mRNA expression.…”
Section: B Regulation Of Histaminementioning
confidence: 99%